The Halal Industry as an Instrument for Strengthening an Inclusive Sharia Economy in Indonesia: An Analysis of Impacts and Challenges - Umi Kulsum; Desy Bariyyatul Qibtiyah (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze the role of the halal industry as an instrument in strengthening an inclusive sharia economy in Indonesia. Although Indonesia has significant potential as a global halal market, the development of the halal industry still faces various obstacles, such as low levels of halal certification, limited access to financing, and disparities among business actors. This study uses a qualitative approach with library research, through a review of various literature in the form of books, scientific articles, and reports from related institutions. The analysis was conducted descriptively and analytically to understand the relationship between the halal industry and an inclusive sharia economy. The results show that the halal industry contributes to increasing economic activity, expanding business opportunities for MSMEs, encouraging sharia financial inclusion, creating jobs, and increasing the competitiveness of Indonesian products in the global market. However, optimizing the role of the halal industry is still hampered by low levels of halal certification, limited access to sharia financing, a suboptimal halal ecosystem, and high global competition. Therefore, it is necessary to strengthen collaboration between the government, Islamic financial institutions, business actors, and the community to build a more integrated halal industry ecosystem that can support the realization of an inclusive and sustainable Islamic economy in Indonesia.